Beta-Cell Fragility As a Common Underlying Risk Factor in Type 1 and Type 2 Diabetes. Issue 2 (February 2017) - Liston, Adrian; Todd, John A.; Lagou, Vasiliki
Abstract : Type 1 and type 2 diabetes are distinct clinical entities primarily driven by autoimmunity and metabolic dysfunction, respectively. However, there is a growing appreciation that they may share an etiopathological factor, namely the role of variation in beta-cell sensitivity to stress factors. Increased sensitivity increases the risk of beta-cell death or insulin secretion dysfunction. The beta-cell fragility model proposes that this variation contributes to the risk of developing either type 1 or type 2 diabetes, in the presence of immunological and/or metabolic stress factors. Therapeutics that increase the resistance of beta cells to these factors and decreasing fragility may constitute a new class of anti-diabetogenics, with potential use across both diseases. Trends: The beta-cell fragility model proposes that variation in beta-cell susceptibility to apoptosis is common to type 1 diabetes (T1D) and late-stage type 2 diabetes (T2D) patients, with individuals possessing more fragile beta-cells being more likely to develop disease. At a genetic level, variants in GLIS family zinc finger 3 ( GLIS3 ) are associated with both T1D and T2D. The function of GLIS3 as an antiapoptotic mediator in beta-cells supports the beta-cell fragility model. The hygiene hypothesis has been proposed to explain the increasing incidence of T1D. However, at an epidemiological level changes in T1D incidence have more in common with obesity and T2D than with other autoimmune disorders. Elevated dietary fat or lipid exposure increases beta-cell susceptibility to apoptosis in animal models and in vitro, providing a mechanistic link between obesity and beta-cell fragility in T1D and late-stage T2D. Video Abstract: